1990
DOI: 10.1021/bi00489a037
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin H synthase: spectroscopic studies of the interaction with hydroperoxides and with indomethacin

Abstract: Prostaglandin H synthase has both a heme-dependent peroxidase activity and a cyclooxygenase activity. A current hypothesis considers the cyclooxygenase reaction to be a free radical chain reaction, initiated by an interaction of the synthase peroxidase with hydroperoxides leading to the production of a tyrosyl free radical [Stubbe, J. A. (1989) Annu. Rev. Biochem. 58, 257-285]. We have examined the kinetics of radical formation with both ethyl hydroperoxide (EtOOH) and 15-hydroperoxyeicosatetraenoic acid (15-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
92
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 33 publications
(54 reference statements)
7
92
0
Order By: Relevance
“…This is in agreement with MS analysis of denitration products from NO 2 -calmodulin where 3-AT formation was not detected (49). With respect to COX-1, studies (6,15,34) have shown that only a small percentage of tyrosine residues (Ïł3 tyrosine residues per COX-1 monomer) are subject to NO x -induced nitration. Although separation and detection of free tyrosine can be achieved by HPLC-ECD, it was difficult to accurately assess whether the 3-NT signal loss was associated with a commensurate formation of new tyrosine residues, owing to A: rat lung homogenate in detergent-free buffer was subjected to differential centrifugation to obtain cellular fractions that are mitochondria rich and mitochondria depleted (as shown in the schematic).…”
Section: Discussionsupporting
confidence: 82%
“…This is in agreement with MS analysis of denitration products from NO 2 -calmodulin where 3-AT formation was not detected (49). With respect to COX-1, studies (6,15,34) have shown that only a small percentage of tyrosine residues (Ïł3 tyrosine residues per COX-1 monomer) are subject to NO x -induced nitration. Although separation and detection of free tyrosine can be achieved by HPLC-ECD, it was difficult to accurately assess whether the 3-NT signal loss was associated with a commensurate formation of new tyrosine residues, owing to A: rat lung homogenate in detergent-free buffer was subjected to differential centrifugation to obtain cellular fractions that are mitochondria rich and mitochondria depleted (as shown in the schematic).…”
Section: Discussionsupporting
confidence: 82%
“…The k 1 value for Compound I formation from EtOOH is a tenth of that for 15-HPETE, and the k 1 for H 2 O 2 is less than a hundredth of that for 15-HPETE (74,75). This suggests that it is the nature of the first few atoms neighboring the hydroperoxide group that is the most important determinant of the rate of Compound I formation.…”
Section: Discussionmentioning
confidence: 96%
“…Indomethacin inhibits COX-1 activity by binding to its active site and subsequently rendering it inactive (25), possibly by producing a conformational change in an essential protein radical (26). Although the mechanisms by which aspirin and indomethacin inhibit COX are different, the relative potencies of these drugs were similar in all of the assays used in this study and in those using microsomal preparations from COS-1 transfected cells for assay of COX-1 and COX-2 activity (19).…”
Section: Discussionmentioning
confidence: 99%